Perception of Artificial Intelligence on the Understanding of Aswaja Courses in IAINU Kebumen Students - Saputri, Anggi Eka; Desmawati, Nurul; A'dilah, Maula; Hawa, Siti Nur; Asfriyantiningsih, Indah; Khumairoh, Umi; Pratama, Imam; Fatimah, Siti; Chamidi, Agus Salim; Najitama, Fikria; Murtajib, Ahmad; Kartika, Nadia Raifah Nawa (Proceeding International Conference on Religion, Science and Education, 2025)
The widespread use of artificial intelligence (AI) tools to support learning has become a pros and cons among academics. Ease of accessing learning materials, including all the information students need to do assignments. This article discusses the influence of artificial intelligence on students' understanding of the Aswaja course. Artificial intelligence (AI) systems can integrate students' progress, spot their weak spots, offer resources and personalized learning suggestions. One of them is helping students to find material or study materials for the Aswaja course. Artificial intelligence (AI) can also help lecturers design lessons and analyze student performance data to engineer new learning interventions and lesson plans. The method used in this research is a quantitative method. The subjects in this research were students at the Nahdlatul Ulama Islamic Institute, Kebumen. Data collection was used using a questionnaire created using Google Forms and distributed online. However, with all the conveniences offered, of course there are concerns about the potential of artificial intelligence to make students independent. Therefore, we need to continue to make placements in using artificial intelligence. AI is used to help us increase our knowledge and make it easier to access learning, not to be used as a dependency in doing all the assignments and exams. Keywords: Artifical Intelligence, Technology, College